Effect of pitfall trap depth on epigaeic beetle sampling (Coleoptera: Carabidae and Staphylinidae) in wet forested ecosites in Alberta, Canada. Issue 6 (24th August 2018) - Hammond, H.E. James; Langor, David W.; Hartley, Dustin J.
Abstract: The depth at which pitfall traps were sunk into the ground and the resulting catches of epigaeic Carabidae (Coleoptera) and Staphylinidae (Coleoptera) assemblages in subhygric to hydric ecosites with very deep organic soil layers was investigated in the upper foothills ecoregion of Alberta, Canada. Traps were installed at seven sites, with six surface traps (the pitfall trap lip <5 cm below soil surface) and six deep traps (the pitfall trap lip >20 cm below soil surface) at each site. A total of 5289 beetles representing 75 taxa were collected. There were no significant effects of trap depth on catch. Rarefaction estimates of species diversity were higher in surface pitfall traps for both taxa. The similarity of pooled catches between deep and surface traps was on average 75%, suggesting that both trap types were collecting similar faunas. We found no advantage to using deep pitfall traps in addition to surface traps to sample the epigaeic fauna of wet forest stands and peatlands.